Automated alert system for river water level and water quality assessment using telegram bot API / Iman Hazwam Abd Halim, Ammar Ibrahim Mahamad and Mohd Faris Mohd Fuzi - Abd Halim, Iman Hazwam; Mahamad, Ammar Ibrahim; Mohd Fuzi, Mohd Faris (UiTM Cawangan Perlis, 2021)
Technology has advanced to the point that it can assist people in their daily lives. Human beings may benefit from this development in a variety of ways. Progress in river water monitoring is also one of them. There are many advantages in improving the river water monitoring system. The objective of this project is to develop an automated system for monitoring river water levels and quality with push notification features. Internet of Things (IoT) was implemented in this research by using NodeMCU as a microcontroller to connect both ultrasonic sensors and pH sensors to the Internet. An ultrasonic sensor is used to read the water level, and a pH sensor is used to read the water pH values. The results show the successful output from all of 10 time attempts to obtain more accurate test results. The results will be averaged to be analysed and concluded from the test. All the tests include testing for the accuracy of the ultrasonic sensor, the accuracy of the pH sensor, and the performance of the internet connection using integrated Wi-Fi module in NodeMCU microcontroller. The system test also shows that it performs perfectly with the requirement needed to send the real-time status of the water level, water quality and an alert to the user using the Telegram Bot API. This research can help to increase the level of awareness of the river water monitoring system. This research was done by looking at people's problems in the vicinity of the river area by producing a system tool that helps to monitor the river water in real-time status.